Estratégias de autenticidade adotadas por influenciadores digitais de baixa renda - Nóbrega, Ana Paula de (2022)
Brazil leads the ranking of Instagram users, behind only the United States (USA). It is a network most used by low-income youth who have their lives transformed by the social networks. Digital Influencers are key to influence decision and purchase intention. They have the challenge to produce authentic content, generate income and value to followers and partners. On the other hand, 78% of followers disapprove advertisements which makes day-to-day of these professionals more challenging. The present study is characterized by low income of digital influencers to identify possible strategies and alternatives that can be used in their content production without losing their authenticity. Through a netnografic research with 31 low-income digital influencers, from different regions of Brazil, we conclude that they express their authenticity when they are faithful to their beliefs and values and community culture where they are inserted. When digital influencers create authentic, original, and creative contents they generate genuine experiences to partners and community and paid partnerships could be perceived as positive by followers. At same time, brands could explore long term partnerships, recruiting influencers that fits genuinely with their brands storytelling and can achieve better results empowering influencers to create content following their personal style and narratives.